تقييم التكوين الجامعي في ضوء معايير الجودة والاعتماد الأكاديمي - نيس, حكيمة (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الحالية إلى الكشف عن العلاقة بين تقييم التكوين الجامعي في ضوء معايير الجودة و الاعتماد الأكاديمي من للمدارس العليا للأساتذة من وجهة نظر طلبتها و بين جودة الأداء الوظيفي لأساتذة التعليم الثانوي خريجي المدارس العليا وفقا لمتغير مادة التدريس (علمية/ أدبية)، وباستخدام المنهج الوصفي وتطبيق المقاييس المناسبة على عينة من أساتذة التعليم الثانوي خريجي المدارس العليا للأساتذة نصفهم يدرسون مواد علمية و نصفهم الآخر يدرس مواد أدبية و بعد تحليل المعطيات أفضت النتائج الى ما يلي: وجود علاقة دالة إحصائيا بين تقييم التكوين الجامعي في ضوء معايير الجودة و الاعتماد الأكاديمي من للمدارس العليا للأساتذة من وجهة نظر طلبتها و بين جودة الأداء الوظيفي لديهم. عدم وجود فروق ذات دلالة إحصائية في تقييم التكوين الجامعي في ضوء معايير الجودة و الاعتماد الأكاديمي من للمدارس العليا للأساتذة من وجهة نظر طلبتها تبعا لمتغير مادة التدريس(علمية/أدبية).عدم وجود فروق ذات دلالة إحصائية في جودة الأداء الوظيفي لأساتذة التعليم الثانوي خريجي المدارس العليا للأساتذة تبعا لمتغير مادة التدريس(علمية/أدبية).و فسرت النتائج في ضوء ما أسفر عنه التراث السيكولوجي والتربوي والدراسات السابقة في الموضوع، وتوجت الدراسة في الأخير بجملة من المقترحات والتوصيات. Abstract: The current study aimed to reveal the relationship between the evaluation of university training in light of quality standards and academic accreditation of higher schools for professors from the point of view of their students and between the quality of job performance of teachers of secondary education graduates of higher schools according to the variable of teaching material (scientific / literary), and by using the descriptive approach And applying appropriate measures to a sample of secondary education professors, graduates of higher schools, for professors, half of whom study scientific subjects and the other half study literary subjects. Higher professors from the viewpoint of their students and the quality of their job performance. The absence of statistically significant differences in the evaluation of university training in light of the quality standards and academic accreditation of higher schools to professors from the viewpoint of their students according to the variable of the teaching material (scientific / literary) The absence of statistically significant differences in the quality of job performance of secondary education teachers, school graduates The results of the study are interpreted in light of the psychological and educational heritage and previous studies on the subject, and the study culminated in the end with a set of proposals and recommendations. variable of the teaching material (scientific / literary). The results were interpreted in the light of the psychological and educational heritage and previous studies on the subject, and the study culminated in the end with a set of proposals and recommendations.
مقال
Keywords: تقييم؛ تكوين الجامعي؛ معايير الجودة؛ جودة األداء الوظيفي؛ أساتذة التعليم الثانو; evaluation; university composition; quality standards; quality of functionality; secondary education teachers.